2019
DOI: 10.1111/febs.15155
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic subunit exchanges in the cellulosomes produced by Ruminiclostridium cellulolyticum suggest unexpected dynamics and adaptability of their enzymatic composition

Abstract: Cellulosomes are complex nanomachines produced by cellulolytic anaerobic bacteria such as Ruminiclostridium cellulolyticum (formerly known as Clostridium cellulolyticum). Cellulosomes are composed of a scaffoldin protein displaying several cohesin modules on which enzymatic components can bind to through their dockerin module. Although cellulosomes have been studied for decades, very little is known about the dynamics of complex assembly. We have investigated the ability of some dockerin‐bearing enzymes to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…As a consequence, the cellulosomes produced display a higher amount of scaffoldins compared with those expressed in presence of oligosaccharides, exposing up to 56 different active GHs on complex substrate. In this context, research on cellulosomes from Ruminiclostridium cellulolyticum has revealed that the conformation of the two domains in dockerins involved in the interaction with cohesins allows the re-functionalization of the cellulosome, and so the exchange between catalytic domains as an adaptation to heterogeneous plant cell wall substrates in active degradation [21]. Furthermore, spatial expression and exposition of cellulosomes on the cell surface varies on substrate used for growth, as exemplified by the cellulosomes produced by Clostridium clariflavum [22].…”
Section: A Large Diversity Of Modularity and Spatial Organizationmentioning
confidence: 99%
“…As a consequence, the cellulosomes produced display a higher amount of scaffoldins compared with those expressed in presence of oligosaccharides, exposing up to 56 different active GHs on complex substrate. In this context, research on cellulosomes from Ruminiclostridium cellulolyticum has revealed that the conformation of the two domains in dockerins involved in the interaction with cohesins allows the re-functionalization of the cellulosome, and so the exchange between catalytic domains as an adaptation to heterogeneous plant cell wall substrates in active degradation [21]. Furthermore, spatial expression and exposition of cellulosomes on the cell surface varies on substrate used for growth, as exemplified by the cellulosomes produced by Clostridium clariflavum [22].…”
Section: A Large Diversity Of Modularity and Spatial Organizationmentioning
confidence: 99%
“…During recent years, these hurdles have slowed down further progress in the DC research field, leading to a decline of studies focusing on the conversion of natural free lignocellulose-active proteins into cellulosomal docking enzymes (DEs). Yet, cellulosome research has shifted focus to (1) the deep understanding of the cellulosomes overall structure and their natural functionality like deciphering natural cellulosome 4 components and architectures that can be incorporated into DCs (Borne et al 2020;Bule et al 2018;Dorival et al 2022;Phitsuwan et al 2019;Tao et al 2022;Vera et al 2021;Zhivin-Nissan et al 2019), studying the mechanical stability of DCs (Galera-Prat et al 2018a), the cohesin-dockerin interaction specificity and affinity (Carvalho et al 2003;Wojciechowski et al 2018) and the role of linkers in DC scaffoldins (Galera-Prat et al 2018b) and (2) on creative engineering tools to lift the DCs applicability in the bio-economy field like engineering hosts for in vivo DC production/assembly (Liu et al 2019;Tao et al 2020;Tarraran et al 2021).…”
Section: Introductionmentioning
confidence: 99%